Strategic uses of social technology an interactive perspective of social psychology - Birchmeier, Zachary; Dietz-Uhler, Beth.; Stasser, Garold; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"On an everyday basis, we communicate with one another using various technological mediums, such as text messaging, social networking tools and electronic mail, in work, educational and personal settings. As a consequence of the increasing frequency of use and importance of computer-supported interaction, social scientists in particular have heeded the call to understand the social processes involved in such interactions. In this volume, the editors explore how aspects of a situation interact with characteristics of a person to help explain our technologically-supported social interactions. The person-by-situation interaction perspective recognizes the powerful role of the situation and social forces on behavior, thought and emotion, but also acknowledges the importance of person variables in explaining social interaction, including power and gender, social influence, truth and deception, ostracism and leadership. This important study is of great relevance to modern readers, who are more and more frequently using technology to communicate with one another"--
Machine generated contents note: 1. Introduction: a social psychological analysis of computer-supported social interaction Zachary Birchmeier, Beth Dietz-Uhler and Garold Stasser; 2. A SIDE look at computer-mediated interaction: power and the gender divide Russell Spears, Martin Lea, Tom Postmes and K. Wolbert; 3. Trust, deception and identity on the Internet Melanie C. Green and Jordan Carpenter; 4. An interactional approach to social influence in computer-mediated communication Kai Sassenberg; 5. Social interaction in cyberspace: social construction with few constraints Susanne Abele; 6. Dynamics of leader emergence in online groups Andrea B. Hollingshead; 7. Ostracism in cyberspace: being ignored and excluded in electronic-based interactions Eric D. Wesselmann and Kipling D. Williams; 8. Opinion-based groups: (racist) talk and (collective) action on the Internet Craig McGarty, Girish Lala and Karen Douglas; 9. A juxtaposition of social influences: Web 2.0 and the interaction of mass, interpersonal, and peer sources online Joseph B. Walther, Stephanie Tom Tong, David DeAndrea, Caleb Carr and Brandon Van Der Heide; 10. The virtual social world: the continually changing landscape of social interaction Zachary Birchmeier, Beth Dietz-Uhler and Garold Stasser.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Social networks -- Psychological aspects; Social interaction; Electronic books